KEANEKARAGAMAN TUMBUHAN ANGIOSPERMAE DI KAWASAN TAMAN NASIONAL MATALAWA KABUPATEN SUMBA TIMUR - Jawaray, Wilfridus Balla; Lalupan, Erfy Melany; Ina, Anita Tamu; Kusumanegara, Agus (Jurnal Biosilampari : Jurnal Biologi, 2023)
The highest plant diversity in the tropical rainforest area in Matalawa National Park is the Angiospermae plant. There are still many people in Praingkareha Village who are not familiar with Angiospermae plants or closed seed plants. This study aims to describe the diversity index of Angiosperm plants found in the Laputi Forest block, Matalawa National Park. This research was limited to the Laputi Forest block, so it did not cover the entire forest in Praingkareha Village, Matalawa National Park, East Sumba Regency. This study used a double plot method with a purposive sampling technique. The results showed that there were 30 species of Angiosperms from 17 families with a total of 499 individuals. The diversity of Angiosperm plants in the Laputi Forest block of the Matalawa National Park area is moderate with (Ĥ)=2.90.